RITUAL TAREI ASYEIK PADA MASYARAKAT KELURAHAN PONDOK TINGGI KOTA SUNGAI PENUH PROVINSI JAMBI - Yolla Ramadani; Nurlizawati Nurlizawati; Salamah Salamah; Yelnim Yelnim (Fikri : Jurnal Kajian Agama, Sosial dan Budaya, 2020)
This article was written to explain why people still perform rituals Tarei Asyeik and describe the process as well as the meaning contained in the ritual Tarei Asyeik. Data were collected through interviews and observations. Asyeik Tarei rituals are still performed by High cottage Village community because the community believes that by carrying out the ritual Tarei Asyeik, they will be protected from any disaster and distress that would threaten their community and not all diseases can be treated medically. Ritual Tarei Asyeik has meaning cleanse and purify the body and soul.